Engaging East Harlem, New York youth in action gun violence prevention research and child rights: a preliminary study - Pallavi Malla; Nakesha Fray; Margaret K. Formica; Danielle Goldberg; Robert Marchesani; Patricia Hennessy; Moshay Ervine; Jacqueline G. Wallace; Elaine Larson; Pamela Wridt; Danielle Laraque-Arena; IAACT (BMC, 2023)
Abstract Background The aim of the study was to have youth participate in the design and implementation of a research project set within a child rights framework to better understand high schoolers' perceptions of safety in their school and community. Results Between June 2020 and March 2021, a team of East Harlem, New York high school students, participated as co-researchers to modify the United Nations Children's Fund Child Friendly Cities Initiative Survey to suit their needs. Due to the COVID-19 pandemic, the final survey was conducted through an online remote classes system during advisory school classes, accompanied by brief focused group discussions. The novel process of conducting an interactive qualitative and quantitative virtual survey during a pandemic via youth participatory action research is outlined in this paper. Conclusions Our results demonstrate that youth participatory action research can be utilized as part of a child rights framework approach to assess the views of youth regarding community safety and violence prevention.